2012
DOI: 10.1161/jaha.112.002246
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Resistance Predicts Myocardial Salvage and Infarct Characteristics in ST‐Elevation Myocardial Infarction

Abstract: Background--The pathophysiology of myocardial injury and repair in patients with ST-elevation myocardial infarction is incompletely understood. We investigated the relationships among culprit artery microvascular resistance, myocardial salvage, and ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 34 publications
4
77
1
Order By: Relevance
“…Myocardial salvage was calculated by subtraction of percentage of infarct size from percentage of area at risk 13, 40. The myocardial salvage index was calculated by dividing the myocardial salvage area by the initial area at risk.…”
Section: Methodsmentioning
confidence: 99%
“…Myocardial salvage was calculated by subtraction of percentage of infarct size from percentage of area at risk 13, 40. The myocardial salvage index was calculated by dividing the myocardial salvage area by the initial area at risk.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, in that study not only patients with primary PCI but also patients with successful thrombolysis or rescue PCI after failed thrombolysis were included. Payne et al 36 showed that IMR was linked to MVI as assessed by CMR in a more homogeneous group of patients with STEMI treated by primary PCI. Doppler-flow velocity is an alternative technique to measure microvascular resistance.…”
Section: Measurements Of Coronary Flow and Microvascular Resistance Imentioning
confidence: 99%
“…Myocardial salvage was calculated by subtraction of percentage infarct size from percentage area at risk, as reflected by the extent of edema 23, 26, 27. The myocardial salvage index was calculated by dividing the myocardial salvage area by the initial area at risk.…”
Section: Methodsmentioning
confidence: 99%